Influence of process conditions of alkalization on quality of cocoa powder - Demirci, Sultan; Elmaci, Ceren; Atalar, Ilyas; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat (ELSEVIER, 2024)
In this study, the effects of independent variables such as alkaline (NaOH) salt concentration (3.0-6.0 g/100 mL), alkalization temperature (60-90 degrees C), and time (20-40 min) on cocoa powder (low-fat) properties were investigated by using Central Composite Design. The physicochemical and color properties of samples, powder characteristics, volatile component profile, total polyphenol content (TPC), as well as antioxidant activity potentials using different methods (DPPH and ABTS) were determined. Significant models were identified for the effects on major alkalization indicators (L*, a*/b*, pH), as well as TPC and antioxidant activity potential (DPPH), which are the main motivators for the preference and consumption of cocoa products (p < 0.05). The established model was validated, and their predicted values were found to be very close to real results. It was determined that the alkali concentration had a more significant effect on dependent variables, especially on alkalization indicators, compared to the other independent variables. Furthermore, strong correlations were determined between TPC and antioxidant activity potential and color properties (L*, a*, b*, and a*/b*). Optimum concentration, temperature and time were found to be 5.3 %, 84 degrees C and 35.7 min for maximizing a*/b* value. The establishment of such models lead to optimizing process conditions of alkalization with minimum effort and labor force for obtaining cocoa powder with desired quality depending on the usage purpose.
Keywords: Alkalization; Cocoa powder; Optimization; Chocolate; Response surface method; INLET TEMPERATURE; ANTIOXIDANT; COLOR; POLYPHENOLS; MILK; Food Science & Technology